Lamotrigine‐induced neutropenia after high‐dose concomitant initiation with phenytoin - Muhammad Salem (8979428) (2023)
Lamotrigine has been repeatedly reported to cause hematologic toxicities, which may be associated with high initial doses or excessive escalation. A 29-year-old lady experienced profound neutropenia after two weeks of lamotrigine high initial dose, started within two days of phenytoin. The too-early dose intensification may have produced lamotrigine-induced blood dyscrasia. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.5136